REGULASI DAN PERKEMBANGAN KEILMUAN TATA SUARA TELEVISI PADA TELEVISI DIGITAL DI INDONESIA - Darmawan, Iwan (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Globalization is changing the world of international regulation of television broadcasting sistem via the ITU (International Telecommunications Universe) forced Indonesia to participate and follow the sistem changes the analog to digital television broadcasting. Familiarization with test broadcasts have been carried by state television through TVRI and followed by other private television stations. Despite opposition from several television stations through the legal migration of digital broadcasting sistems will still be done. Specifications DVB-T2 broadcasting sistem using the mpeg2 format allows the television voice accompanied by surround encoding format that is commonly used in the cinema (film). So the need for additional professional expertise audio department must be conducted in accordance with the development of television broadcasting in digital audio technology.